Non‐invasive detection of genome‐wide somatic copy number alterations by liquid biopsies1. Issue 3 (17th December 2015) - Heitzer, Ellen; Ulz, Peter; Geigl, Jochen B.; Speicher, Michael R.
Abstract : Liquid biopsies, i.e. the analysis of circulating tumor cells (CTCs) or circulating tumor DNA (ctDNA), are evolving into promising clinical tools. Indeed, a plethora of liquid biopsy technologies to deduce non‐invasively characteristics of the tumor genome from the peripheral blood have been developed over the last few years. For example, liquid biopsies have been used to assess the tumor burden, to monitor the evolution of tumor genomes, to unravel mechanisms of resistance, to establish the tumor heterogeneity, and for the identification of prognostic and predictive markers. In this review we focus on methods to establish genome‐wide profiles of somatic copy number alterations (SCNAs) from plasma DNA and show how they provide novel insights into the biology of cancer and their impact on the management of patients. Highlights: The analysis of circulating tumor cells (CTCs) or circulating tumor DNA (ctDNA) are evolving into promising clinical tools. Novel methods allow establishing non‐invasively genome‐wide profiles of somatic copy number alterations (SCNAs) from ctDNA. Analyzing the evolution of SCNAs is important as it may alter the status of oncogenes (OGs) or tumor suppressor genes (TGs).